A case series of transcatheter Potts Shunt creation in a pediatric population affected with refractory pulmonary artery hypertension: focus on the role of ECMO. (May 2021) - Mirabile, Cristian; Malekzadeh-Milani, Sophie; Bojan, Mirela; Raisky, Olivier; Gaudin, Regis; Bonnet, Damien; Boudjemline, Younes
Purpose: Patients with suprasystemic idiopathic pulmonary hypertension (S-PAH) have a poor prognosis. Therapeutic options are limited. Reverse Potts shunt creation modifies physiology transforming patients with PAH into Eisenmenger physiology with a better outcome. Percutaneous transcatheter stent secured aortopulmonary connection (transcatheter Potts Shunt, TPS) is a feasible very high-risk procedural option in such patients. We report our experience with patients undergoing TPS at our institution requiring extracorporeal membrane oxygenation (ECMO) support. Methods: A prospective observational study of patients with drug-refractory PAH, worsening NYHA class, and right ventricular failure undergoing TPS. Two patients required rescue ECMO for cardiac arrest during the procedure. Subsequently, "standby ECMO" was available in all the following cases and elective support was provided in patients with extremely poor conditions. Results: Ten pediatric patients, underwent TPS at our institution. Two patients were rescued by ECMO after cardiac arrest during the shunt creation. This occurred as a result of the acute loading of the left ventricle (LV) after retrograde aortic arch filling through the Potts shunt. Following this, another two patients underwent elective ECMO after the uneventful induction of anesthesia. They all died postoperatively despite a successful TPS procedure. The causes of death were not related to the use of ECMO, but the complication of severe PAH. Six patients with successful TPS did not require ECMO and survived. Conclusions: TPS is a pioneering procedure offering the opportunity to treat high-risk idiopathic drug-refractory PAH patients. Acute LV failure is a complication of TPS in patients with S-PAH. Elective ECMO, an option to avoid circulatory arrest and acute profound hypoxia secondary to exclusive right-to left shunt systemic perfusion by Potts shunt and LV dysfunction with resulting pulmonary edema, may be used at the early stage of the learning curve, but it does not influence the prognosis of these patients which remains poor.